'Opening up' Education Policy Making in England – Space for Ordinary Citizens' Participation?. Issue 2 (3rd April 2021) - Exley, Sonia
ABSTRACT: This article explores UK attempts to boost ordinary citizens' participation in government policy formulation through 'open policy making'. Drawing primarily on an analysis of government documents dating from 2012–2018 and focusing on the case of the Department for Education in England, the article highlights elite network control of policy making which works to depress ordinary citizens' democratic input. Groups who do not fit with depoliticised, 'top down' understandings of what counts as valid citizen participation become delegitimised and excluded.